A Matlab program and user's guide for the fractionally cointegrated VAR model - Morten Ørregaard Nielsen; Michał Ksawery Popiel (Queen's University, Department of Economics, 2014)
This manual describes the usage of the accompanying freely available Matlab program for estimation and testing in the fractionally cointegrated vector autoregressive (FCVAR) model. This program replaces an earlier Matlab program by Nielsen and Morin (2014), and although the present Matlab program is not compatible with the earlier one, we encourage use of the new program.
Keywords: C22; C32; 330; cofractional process; cointegration rank; computer program; fractional autoregressive model; fractional cointegration; fractional unit root; Matlab; VAR model